2015
DOI: 10.1002/cncr.29530
|View full text |Cite
|
Sign up to set email alerts
|

Patient perceptions regarding the likelihood of cure after surgical resection of lung and colorectal cancer

Abstract: BACKGROUND The objective of the current study was to characterize the prevalence of the expectation that surgical resection of lung or colorectal cancer might be curative. The authors sought to assess patient-level, tumor-level, and communication-level factors associated with the perception of cure. METHODS Between 2003 and 2005, a total of 3954 patients who underwent cancer-directed surgery for lung (30.3%) or colorectal (69.7%) cancer were identified from a population-based and health system-based survey o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
40
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 53 publications
(43 citation statements)
references
References 40 publications
(97 reference statements)
3
40
0
Order By: Relevance
“…4,22,27 To this point, our group has shown using the same cohort of patients that 57.4 % with metastatic lung cancer and 79.8 % of patients with metastatic colon cancer believed surgery to be curative. 14 Given this, it appears that patient misconceptions about cure with regards to cancer, and in particular advanced metastatic cancer, may either be due in part to patient misunderstanding or a failure of the physician to effectively communicate and help patients understand their true prognosis. In fact, our results regarding the association of excellent physician communication and excellent quality of care support findings from Roberts et al who reported that empathy from surgeons was the most important factor to cancer patients as opposed to information-giving.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…4,22,27 To this point, our group has shown using the same cohort of patients that 57.4 % with metastatic lung cancer and 79.8 % of patients with metastatic colon cancer believed surgery to be curative. 14 Given this, it appears that patient misconceptions about cure with regards to cancer, and in particular advanced metastatic cancer, may either be due in part to patient misunderstanding or a failure of the physician to effectively communicate and help patients understand their true prognosis. In fact, our results regarding the association of excellent physician communication and excellent quality of care support findings from Roberts et al who reported that empathy from surgeons was the most important factor to cancer patients as opposed to information-giving.…”
Section: Discussionmentioning
confidence: 99%
“…All patients including patients with metastatic disease (stage IV) were included in this study as previous studies have shown that patients with advanced disease often have unrealistic perceptions of cure. 14 Patient-reported assessment of quality of care, role in decision-making, patient – physician communication, and perceptions about potential beneficial and adverse effects of surgical treatment were derived from CanCORS survey questions and categorized as previously described (Supplementary Table S1) 4,6,15 . Assessment of physician communication skills was calculated from five survey items that were derived from the Consumer Assessment of Healthcare Providers and Systems (CAHPS), with an indication 0 as the worst possible communication and 100 as optimal communication.…”
Section: Methodsmentioning
confidence: 99%
“…Findings from a study of patients’ expectations about chemotherapy showed that more than two-thirds of patients with lung or colorectal cancers thought their palliative chemotherapy, 2 radiation, 3 and/or surgery 4 could cure them. Failure to effectively educate patients can lead to end-of-life care associated with poor quality of care, including over-aggressive care, poor quality of life with suboptimal symptom management, caregiver distress, and other potentially preventable problems.…”
mentioning
confidence: 99%
“…1 The data also suggest that metrics of “good” communication, which rely on participant perception and/or satisfaction, should not necessarily be used as indicators of “complete” communication with respect to the content that patients and surgeons want and need to convey. We commend the efforts of Blazeby et al in establishing core information sets for cancer surgery, which have been formulated with the involvement of key stakeholders in surgical decision-making, and which can serve as an indicator of “complete” communication.…”
mentioning
confidence: 99%
“…1 We share their concern that insufficient information exchange between the patient and surgeon may compromise a patient’s ability to make an informed decision and may leave open the possibility that the patient may select a treatment course that is inconsistent with their treatment goals.…”
mentioning
confidence: 99%